(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Kerala, the ―Land of Spices‖, has a rich culinary heritage influenced by its geography, climate, culture, and historical factors. Kerala’s cuisine is characterized by the use of spices, coconut, rice, and locally grown vegetables, fruits, and seafood. Rice is a staple food, and coconut is a prominent ingredient in Kerala cuisine. Kerala’s coastline provides access to a variety of seafood, including fish, shrimp, crab, and mussels. The cuisine strikes a balance between heat and flavours, using a variety of vegetables and proteins. Keralites enjoy a variety of snacks, including sweet and savoury options. Kerala also offers a range of breakfast options, including steamed rice cakes, appam, string hoppers, and dosa. Ayurvedic principles influence Kerala’s dietary practices, emphasizing the balance of flavours, nutrition, and health benefits.